Integration of Commercial Screen‐printed Electrodes into a Voltammetric Electronic Tongue for the Analysis of Aminothiols. Issue 7 (23rd February 2016) - Pedroza, Ricardo H. P.; Serrano, Núria; Díaz‐Cruz, José Manuel; Ariño, Cristina; Esteban, Miquel
Abstract: A voltammetric sensor array (or electronic tongue) is developed for the simultaneous quantification of cysteine, glutathione and homocysteine without need of previous separation. It is based on the integration of three commercial screen‐printed electrodes (gold curated at high and low temperature and carbon modified with carbon nanotubes). Linear sweep voltammograms measured simultaneously by all three sensors are processed by Partial Least Squares (PLS) regression and different variables selection algorithms such as Genetic Algorithm and interval‐Partial Least Squares. The method was applied to synthetic mixtures and successfully validated, with correlation coefficients of prediction (Rp 2 ) of 0.9542, 0.9429 and 0.9589 for cysteine, glutathione, and homocysteine respectively. Abstract :